SPATIAL-TEMPORAL DISTRIBUTION OF AQUATIC INSECTS IN STREAMS OF THE AMAZON LOWLANDS, LORETO, PERU - Alvan Aguilar, Miriam Adriana (2022)
This study aimed to determine the spatial and temporal distribution of aquatic insects in 10 streams of the Amazon lowlands located within the area of ​​influence of the Iquitos-Nauta highway (Loreto, Peru). Samplings were made in two zones with different access roads, anthropic influence and stream sizes, which were named: ZM 1 and ZM 2; and, during three distinct hydrological periods: draining season, dry season and rising season. Richness, abundance, diversity, and dominance of aquatic insects; as well as water pH, temperature (ºC), dissolved oxygen (mg/l) and electrical conductivity (μS/cm) levels of each stream were recorded. Results report a total richness of 63 families and 4771 individuals; of which the families Leptophlebiidae, Caenidae, Libellulidae, Hidrophilidae, Elmidae, Hydropsychidae, Polycentropodidae, Tipulidae, Ceratopogonidae and Chironomidae, are widely distributed in the evaluated streams. Significant differences were recorded between the two sampling areas (p=0.01) and among the three collection periods evaluated (p=0.035); reporting higher records of richness, abundance and diversity; as well as higher values ​​of pH, temperature, dissolved oxygen and electrical conductivity in the streams of the ZM 2 and during the dry season. The highest level of dominance occurred in the streams of ZM 1, during the draining and rising water seasons, being Chironomidae, the dominant family. Our results provide baseline information for the optimization of methods for evaluating the environmental quality of streams in the Peruvian Amazon lowlands.